Fungal Involvement in Biodeterioration of Ancient Monuments: Problem and Prospects - Motilal3, Kavita Sharma1*, K.P. Verma2, (Journal of Phytology, 2011)
The air contains a large amount of biological and a biotic component such as, pollen grains, fungal spores, insects, mites, fibers and dust particles but their number and concentration depend upon the geographical location, types of vegetation and meteorological parameters. Fungal ability in production of pigments and organic acids have crucial role in discoloration and degradation of different types of stone in cultural heritage objects. Additionally, stone objects may support novel communities of microorganisms that are active in Biodeterioration process. The problem of deterioration of ancient monuments caused by Microbial agent, of which fungi play an important role in the deterioration. Present investigation focuses on mycobial survey of The Temple group of Satmahla (Surguja region) and study carried out March 2010 to February 2011. During the investigation period 24 fungal species were isolated from the surface of monument which are Aspergillus, Penicillium, Curvularia, Cladosporium, Fusarium and Rhizopus. reported as dominant fungal type in tample of Satmahla.